2016
DOI: 10.1038/srep29328
|View full text |Cite
|
Sign up to set email alerts
|

High Thermal Gradient in Thermo-electrochemical Cells by Insertion of a Poly(Vinylidene Fluoride) Membrane

Abstract: Thermo-Electrochemical cells (Thermocells/TECs) transform thermal energy into electricity by means of electrochemical potential disequilibrium between electrodes induced by a temperature gradient (ΔT). Heat conduction across the terminals of the cell is one of the primary reasons for device inefficiency. Herein, we embed Poly(Vinylidene Fluoride) (PVDF) membrane in thermocells to mitigate the heat transfer effects - we refer to these membrane-thermocells as MTECs. At a ΔT of 12 K, an improvement in the open ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The lower output power as compared with our measured value may be attributed to lack of ionic liquid in their gel electrolyte. Hasan et al reported the maximum power output of 245 n W /m 2 in membrane-inserted thermoelectrochemical cells (MTECs) with Seebeck coefficient of 0.4 mV/K but still, leakage problem exists due to the liquid state of electrolytes [58]. Our measured value of Power output is close to their value with higher Seebeck coefficient of 1.38 mV/K and no leakage issue because of the solid state of X-TEHIG.…”
Section: Power and Current Outputsupporting
confidence: 72%
See 1 more Smart Citation
“…The lower output power as compared with our measured value may be attributed to lack of ionic liquid in their gel electrolyte. Hasan et al reported the maximum power output of 245 n W /m 2 in membrane-inserted thermoelectrochemical cells (MTECs) with Seebeck coefficient of 0.4 mV/K but still, leakage problem exists due to the liquid state of electrolytes [58]. Our measured value of Power output is close to their value with higher Seebeck coefficient of 1.38 mV/K and no leakage issue because of the solid state of X-TEHIG.…”
Section: Power and Current Outputsupporting
confidence: 72%
“…where ZT is figure of merit, S is Seebeck coefficient also called thermopower (VK -1 ), σ is electrical conductivity (S m -1 ), K is thermal conductivity (W/ (m K), T is absolute temperature (K) and S 2 σ is called power factor (Wm -1 K -2 ). In order to get high ZT, the materials must possess higher Seebeck coefficient and electrical conductivity along with lower thermal conductivity [6][7][8][9]. The higher values of Seebeck coefficient will be accompanied by high voltage output, high electrical conductivity will reduce the Joule heating, and lower thermal conductivity will maintain large temperature gradients in TE modules [10,11].…”
Section: Zt = (S 2 σT)/kmentioning
confidence: 99%
“…At this point, ILs' influence on the redox couples must be understood so can obtain higher Seebeck coefficients. In 1968, for the first time Cornwell, et al showed the use of ILs in TECs, but the ILs' effects were not fully understood [102]. In 1980, Chum, et al contributed with a similar study [103].…”
Section: Se= ∂E/ ∂T = −∆S/nf (5)mentioning
confidence: 99%
“…While these are extremely useful and can be used to quantify the device performance, they provide little information on the processes occurring within the electrolyte and certainly no insights into spatial variations in the cell. Said and co-workers have used infrared thermal imaging to study the temperature distribution across thermocells incorporating polymer membranes [25], but these images could only provide the temperature across the outer surface of the device.…”
Section: Introductionmentioning
confidence: 99%